2014
DOI: 10.1007/s11033-014-3498-6
|View full text |Cite
|
Sign up to set email alerts
|

PTPN22 1858C>T gene polymorphism in patients with SLE: association with serological and clinical results

Abstract: To assess the association between PTPN22 1858C>T gene polymorphism and susceptibility to, and clinical presentation of, systemic lupus erythematosus (SLE). Our study included 135 SLE patients (120 women and 15 men; mean age 45.1 years; mean course of disease from 0.5 to 31 years) and 201 healthy subjects. The PTPN22 1858C>T gene polymorphism was genotyped by polymerase chain reaction restriction fragment length polymorphism. A significantly higher incidence of genotype CT in patients with SLE (36.3 %) was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…The association with SLE has now been replicated in nearly 20 studies, and 2 recent meta‐analyses showed an overall odds ratio of ~1.5 . SLE patients with an 1858T allele were noted in different studies to have higher interferon‐α (IFNα) levels and lower TNF levels , somewhat more prevalent nephritis , and a higher incidence of antiphospholipid syndrome with anticardiolipin autoantibodies .…”
Section: Ptpn22 In Slementioning
confidence: 95%
“…The association with SLE has now been replicated in nearly 20 studies, and 2 recent meta‐analyses showed an overall odds ratio of ~1.5 . SLE patients with an 1858T allele were noted in different studies to have higher interferon‐α (IFNα) levels and lower TNF levels , somewhat more prevalent nephritis , and a higher incidence of antiphospholipid syndrome with anticardiolipin autoantibodies .…”
Section: Ptpn22 In Slementioning
confidence: 95%
“…A missense C1858T single‐nucleotide polymorphism (SNP) in PTPN22 encodes an arginine‐to‐tryptophan substitution–bearing protein variant (R620W or LypW) that confers disease risk. Although LypW carriage is associated with modestly altered frequencies of antiphospholipid antibodies and renal disease in SLE patients, clinical phenotypes do not offer strong clues to the mechanism(s) whereby the variant increases disease risk .…”
mentioning
confidence: 99%
“…PTPN22 C1858T polymorphism has been associated with the pathogenesis of SLE in various populations ( Table 7). This polymorphism is significantly associated with susceptibility to SLE in American [116][117][118], Columbian [86,87], Crete [119], Spanish [96], Swedish [120], Polish [121,122], Egyptian populations [123,124].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%